A Ffowcs Williams and Hawkings formulation for hydroacoustic analysis of propeller sheet cavitation. (20th January 2018) - Testa, C.; Ianniello, S.; Salvatore, F.
Abstract: A novel hydroacoustic formulation for the prediction of tonal noise emitted by marine propellers in presence of unsteady sheet cavitation, is presented. The approach is based on the standard Ffowcs Williams and Hawkings equation and the use of transpiration (velocity and acceleration) terms, accounting for the time evolution of the vapour cavity attached on the blade surface. Drawbacks and potentialities of the method are tested on a marine propeller operating in a nonhomogeneous onset flow, by exploiting the hydrodynamic data from a potential-based panel method equipped with a sheet cavitation model and comparing the noise predictions with those carried out by an alternative numerical approach, documented in literature. It is shown that the proposed formulation yields a one-to-one correlation between emitted noise and sheet cavitation dynamics, carrying out accurate predictions in terms of noise magnitude and directivity.